Health care experiences of pregnant, birthing and postnatal women of color at risk for preterm birth. (March 2018) - McLemore, Monica R.; Altman, Molly R.; Cooper, Norlissa; Williams, Shanell; Rand, Larry; Franck, Linda
Abstract: Background: Chronic stress is a known risk factor for preterm birth, yet little is known about how healthcare experiences add to or mitigate perceived stress. In this study, we described the pregnancy-related healthcare experiences of 54 women of color from Fresno, Oakland, and San Francisco, California, with social and/or medical risk factors for preterm birth. Methods: This study was a secondary analysis of focus group data generated as part of a larger project focused on patient and community involvement in preterm birth research. English and Spanish speaking women, age 18 or greater with social and/or medical risk factors for preterm birth participated in two focus groups, six weeks apart. Data from the first focus groups are included in this analysis. Results: Five themes emerged from thematic analysis of the transcripts. Participants described disrespect during healthcare encounters, including experiences of racism and discrimination; stressful interactions with all levels of staff; unmet information needs ; and inconsistent social support . Despite these adverse experiences, women felt confidence in parenting and newborn care . Participant recommendations for healthcare systems improvement included: greater attention to birth plans, better communication among multiple healthcare providers, more careful listening to patients during clinical encounters, increased support for social programs such as California's Black Infant Health, and less reliance on past carceral history and/or child protective services involvement. Discussion: The women in this study perceived their prenatal healthcare as a largely disrespectful and stressful experience. Our findings add to the growing literature that women of color experience discrimination, racism and disrespect in healthcare encounters and that they believe this affects their health and that of their infants. Highlights: Women of color at risk for preterm birth have stressful healthcare experiences. Social service and healthcare delivery system coordination should be improved. Multiple factors influence how people perceive their healthcare seeking experiences.